Molecular Genetic Analysis of Glucan Branching Enzymes from Plants and Bacteria in Arabidopsis Reveals Marked Differences in Their Functions and Capacity to Mediate Starch Granule Formation . Issue 3 (10th September 2015) - Lu, Kuan-Jen; Streb, Sebastian; Meier, Florence; Pfister, Barbara; Zeeman, Samuel C.
Abstract : Expressing glucan branching enzymes from different plants and bacteria in branching enzyme-deficient Arabidopsis plants reveals marked differences in their specificity, yielding unique starch structures. Abstract: The major component of starch is the branched glucan amylopectin, the branching pattern of which is one of the key factors determining its ability to form semicrystalline starch granules. Here, we investigated the functions of different branching enzyme (BE) types by expressing proteins from maize ( Zea mays BE2a), potato ( Solanum tuberosum BE1), and Escherichia coli (glycogen BE [EcGLGB]) in Arabidopsis ( Arabidopsis thaliana ) mutant plants that are deficient in their endogenous BEs and therefore, cannot make starch. The expression of each of these three BE types restored starch biosynthesis to differing degrees. Full complementation was achieved using the class II BE ZmBE2a, which is most similar to the two endogenous Arabidopsis isoforms. Expression of the class I BE from potato, StBE1, resulted in partial complementation and high amylose starch. Expression of the glycogen BE EcGLGB restored only minimal amounts of starch production, which had unusual chain length distribution, branch point distribution, and granule morphology. Nevertheless, each type of BE together with the starch synthases and debranching enyzmes were able to create crystallization-competent amylopectin polymers. These data add to the knowledge of how the properties of the BE influence the final composition of starch and fine structure of amylopectin.